Identification of salivary N‐glycoproteins and measurement of glycosylation site occupancy by boronate glycoprotein enrichment and liquid chromatography/electrospray ionization tandem mass spectrometry. (27th January 2014) - Xu, Ying; Bailey, Ulla‐Maja; Punyadeera, Chamindie; Schulz, Benjamin L.
<x xml:space="preserve">Abstract</x> RATIONALE Diseases including cancer and congenital disorders of glycosylation have been associated with changes in the site‐specific extent of protein glycosylation. Saliva can be non‐invasively sampled and is rich in glycoproteins, giving it the potential to be a useful biofluid for the discovery and detection of disease biomarkers associated with changes in glycosylation. METHODS Saliva was collected from healthy individuals and glycoproteins were enriched using phenylboronic acid based glycoprotein enrichment resin. Proteins were deglycosylated with peptide‐N‐glycosidase F and digested with AspN or trypsin. Desalted peptides and deglycosylated peptides were separated by reversed‐phase liquid chromatography and detected with on‐line electrospray ionization quadrupole‐time‐of‐flight mass spectrometry using a 5600 TripleTof instrument. Site‐specific glycosylation occupancy was semi‐quantitatively determined from the abundance of deglycosylated and nonglycosylated versions of each given peptide. RESULTS Glycoprotein enrichment identified 67 independent glycosylation sites from 24 unique proteins, a 3.9‐fold increase in the number of glycosylation sites identified. Enrichment of glycoproteins rather than glycopeptides allowed detection of both deglycosylated and nonglycosylated versions of each peptide, and thereby robust measurement of site‐specific occupancy at 21 asparagines. Healthy individuals showed limited biological variability in occupancy, with partially modified sites having characteristics consistent with inefficient glycosylation by oligosaccharyltransferase. Inclusion of negative controls without enzymatic deglycosylation controlled for spontaneous chemical deamidation, and identified asparagines previously incorrectly annotated as glycosylated. CONCLUSIONS We developed a sample preparation and mass spectrometry detection strategy for rapid and efficient measurement of site‐specific glycosylation occupancy on diverse salivary glycoproteins suitable for biomarker discovery and detection of changes in glycosylation occupancy in human disease. Copyright © 2014 John Wiley & Sons, Ltd.